Retrospective study of patients with Chiari: malformation submitted to surgical treatment Estudo retrospectivo de pacientes com malformação de Chiari tratados cirurgicamente - Mário Augusto Taricco; Luiz Ricardo Santiago Melo (Arquivos de Neuro-Psiquiatria)
The Chiari malformation (CM) is characterized by variable herniation of one or both cerebellar tonsils, associated or not with displacement of the hindbrain structures into the vertebral canal. This is a retrospective study of 29 patients with CM submitted to surgical procedure between 1990 and 2003. There were 14 females and 15 males whose ages ranged from 16 to 65 years. There were seven patients with isolated CM, 12 associated with syringomyelia (SM), three associated with basilar impression (BI) and seven associated with SM and BI. The surgery was based on posterior fossa decompression. In seven patients a catheter was introduced from the subarachnoid space into the III ventricle and five were submitted to tonsillectomy. Twenty-one patients improved, one worsened, one remained unchanged, four missed follow up and two died. We conclude that the best results with CM surgery are obtained by an effective posterior fossa decompression. Those CM cases associated with other abnormalities, such as SM and BI, probably need complementary techniques which will be the theme for new prospective studies. A malformação de Chiari (MC) é o deslocamento variável de uma ou ambas as tonsilas cerebelares para o canal vertebral. Este trabalho é um estudo retrospectivo de pacientes com MC tratados com cirurgia de 1990 até 2003. Foram analisados 29 prontuários, sendo 15 pacientes do sexo masculino e 14 do feminino, com idade variando entre 16 a 65 anos. Destes, sete só apresentavam MC, 12 tinham MC associada com siringomielia (SM), três associada com impressão basilar (IB) e sete associada com SM e IB. Foi realizada descompressão da fossa posterior e plástica da dura-máter em todos. Em sete pacientes, foi acrescida a colocação de catéter do espaço subaracnóideo para o interior do IV ventrículo e em cinco a tonsilectomia. Ocorreu melhora dos sintomas em 21 pacientes, um permaneceu inalterado, houve piora em um caso, quatro não tiveram seguimento e dois faleceram. Conclui-se que a boa evolução da MC está relacionada com a descompressão efetiva da fossa posterior. Os casos de MC associadas a outras malformações, como IB e SM, talvez necessitem variações técnicas, as quais serão temas de novos estudos prospectivos.